Kendali Kecepatan Motor DC dengan Metode Pulse Width Modulation menggunakan N-channel Mosfet - Suhendra, Tonny; Uperiati, Alena; Purnamasari, Dwi Amalia; Yunianto, Anton Hekso (Jurnal Sustainable: Jurnal Hasil Penelitian dan Industri Terapan, 2018)
The DC motor is one component of robot, the main function of a DC motor is as a driver, whether its a legged robot or not, as used in a mobile robot. DC motor control is necessary to be one thing that must be considered, because if the motor does not run properly, it will renew the purpose of the motor when it is created. The ability to control a DC motor is needed when building a robot. Many things can affect a personâs ability to design DC motor controller, one of which is the development of science, especially computer science, the use of algorithms to achieve the effectiveness of DC motor movements is very necessary today, so that the robot can move well and according to what is desired. The algorithm requires some information from the system that is built either as input or output so that the algorithm can perform the control process properly. in this study the motor speed controller circuit has been designed using transistor IR630 (n-channel mosfet), in this study the motor speed controller circuit has been designed using transistor IR630 (n-channel mosfet), the potentiometer is used as an analog input on the microcontroller and then converted to a PWM signal which will be used as input to the controller circuit to drive a DC motor. In the tests that have been carried out, the results obtained that the motor can be controlled properly, the use of resistors with a certain amount (220 ohms) can increase the resulting motor rotation and at what voltage the motor starts to spin at a voltage of 0.436 volts, and continues to increase and the maximum voltage recorded at 6.40 Volts.